2021
DOI: 10.1007/s00300-021-02843-2
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA gene and 18S rRNA gene diversity in microbial mat communities in meltwater ponds on the McMurdo Ice Shelf, Antarctica

Abstract: The undulating ice of the McMurdo Ice Shelf, Southern Victoria Land, supports one of the largest networks of ice-based, multiyear meltwater pond habitats in Antarctica, where microbial mats are abundant and contribute most of the biomass and biodiversity. We used 16S rRNA and 18S rRNA gene high-throughput sequencing to compare variance of the community structure in microbial mats within and between ponds with different salinities and pH. Proteobacteria and Cyanobacteria were the most abundant phyla, and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
(78 reference statements)
7
19
0
Order By: Relevance
“…In a study comparing McMurdo Dry Valleys' microbial mat communities exposed to different environmental factors, salinity was the best predictor for community composition, followed by temperature and pH [107]. More specifically, Cyanobacteria dominated the mats in high salinity ponds, with Pseudanabaenales replacing Phormidiaceae as the dominant family in these conditions.…”
Section: Factors Impacting the Mat Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study comparing McMurdo Dry Valleys' microbial mat communities exposed to different environmental factors, salinity was the best predictor for community composition, followed by temperature and pH [107]. More specifically, Cyanobacteria dominated the mats in high salinity ponds, with Pseudanabaenales replacing Phormidiaceae as the dominant family in these conditions.…”
Section: Factors Impacting the Mat Communitiesmentioning
confidence: 99%
“…Thus, Cyanobacteria provide substrates and nutrients for the rest of the community, which in turn are capable of degrading those compounds. However, multiple studies of the Antarctic mats show that Proteobacteria (mostly Alphaproteobacteria and Betaproteobacteria) and Bacteroidetes are often equally found, if not more abundant [7,[107][108][109][110]. In fact, a study comparing the Artic and Antarctic bacterial mats revealed the same high abundance of Proteobacteria on both poles and similar overall community composition [110].…”
Section: Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagenomic and small subunit rRNA gene studies have confirmed microscopy surveys identifying diverse and highly productive cyanobacterial communities in the 'dirty ice' of the McMurdo Ice Shelf (Varin et al, 2012;Jackson et al, 2021). Major taxa comprise the heterocyte forming genera Anabaena, Nostoc, and Nodularia and filamentous non-heterocyte forming genera including Oscillatoria, Phormidium, Pseudanabaena, and Leptolyngbya (Jungblut et al, 2005;Varin et al, 2012;Jackson et al, 2021).…”
Section: Introductionmentioning
confidence: 88%
“…To date, studies of Antarctic ponds have given insight into the structure of communities forming dense microbiological mats (Fernández-Valiente et al, 2001;Peeters et al, 2011Peeters et al, , 2012Sutherland et al, 2020;Jackson et al, 2021), lining mats of benthic zone and sediments (Archer et al, 2015;Callejas et al, 2018), and phytoplankton (Vinocur and Unrein, 2000;Allende and Mataloni, 2013;Archer et al, 2014). A limited study was conducted to characterize microbial communities in water columns (Archer et al, 2016) and determine their metabolic properties (Ferrés et al, 2015).…”
Section: Introductionmentioning
confidence: 99%